Pelatihan Membuat E-Book Memanfaat Aplikasi Canva Pada Siswa SD Di Desa Patemon - Sumardiyanto Sumardiyanto; Agusti Agusti; M Maulidan Abi A; Achmad Fawaid; Budi Purnawan; Vita Nur Sihinda; Arini Hidayati (Lembaga Pengembangan Kinerja Dosen, 2024)
It is natural that science and technology are currently developing, therefore it is required to be able to determine appropriate learning methods and media to facilitate the teaching and learning process. Until now, the selection and fulfillment of technology-based learning media is still very rarely carried out and implemented. To develop learning media for PBPMD student activities in Patemon village, namely holding community service where the main program is training in making e-books or digital books using multimedia applications as learning media in elementary schools in Patemon village. To maximize the use of Information and Technology (IT)-based media in learning and the supporting facilities available, training and assistance in creating IT-based media is carried out so that education in villages, especially Petemon village, also competes in IT developments.